Repeating ourselves the brave new world of cloning - Horn, Kristii (New York : Knowledge Unlimited, 1999)
Disscussed on the making of Dolly. How to clone a sheep. Dolly the sheep was born in July of 1996. She was the first mammal cloned from an adult animal. This is how scientists at the Roslin Institute in Scotland used the cells of adult sheep to make Dolly
Writer, Linda Endsley ; series director, Liza Diprima
Narrator: Buzz Kemper
Keywords: Cloning -- Moral and ethical aspects; Dolly (Sheep); Human reproductive technology -- Moral and ethical aspects